PEMBERDAYAAN EKONOMI MASYARAKAT MELALUI KERAJINAN RAJUT DESA SUMBEREJO KECAMATAN TRUCUK KABUPATEN BOJONEGORO - M. Romadlon Habibullah (Mafaza : Jurnal Pengabdian Masyarakat, 2021)
The university is part of the intellectual community in this country, which is expected to be able to contribute to the development of the nation and state. Community Service Activities (PKM) are a form of education by providing empirical experience to Lecturers with students to live in the midst of society outside the campus, and directly teaching students how to identify populist social problems. Sumberejo Village is a village located in Trucuk District, Bojonegoro, East Java. The implementation of the Covid-19 Thematic PKM activity was carried out in Sumberejo Village because the PKM location was an area close to student homes. In accordance with the direction of the Institute for Research and Community Service (LPPM) at the University of Nahdlatul Ulama Sunan Giri Bojonegoro that the implementation of PKM is better in their respective villages to reduce mobility and transmission of COVID-19. PKM in Sumberejo Village Using a Community Based Research approach, by carrying out a community assistance process using the Asset Based Community Development (ABCD) method. The 2021 Thematic PKM activity at the Sunan Giri Bojonegoro University Nahdlatul Ulama in Sumberejo Village, Trucuk District can be carried out well. Activities can be accepted by the community and receive support from all levels of village officials and several elements who are always enthusiastic about ongoing activities. Work programs that are focused on community economic development during the pandemic. The activity is in the form of developing yarn knitting skills. Marketing assistance for community knitting products, namely on social media and marketplaces. Marketing and introducing knitting products in Sumberajo Village which was carried out after development assistance.